2020
DOI: 10.3390/ijms21082822
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Porins and β-Lactamase in Outer Membrane Vesicles on the Hydrolysis of β-Lactam Antibiotics

Abstract: Gram-negative bacteria have an outer membrane inhibiting the entry of antibiotics. Porins, found within the outer membrane, are involved in regulating the permeability of β-lactam antibiotics. β-lactamases are enzymes that are able to inactivate the antibacterial properties of β-lactam antibiotics. Interestingly, porins and β-lactamase are found in outer membrane vesicles (OMVs) of β-lactam-resistant Escherichia coli and may be involved in the survival of susceptible strains of E. coli in the presence of antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…In order to perform docking, the three-dimensional X-ray crystal structure of E. coli β-lactamase (PDB ID: 4E3K, resolution = 1.43Å) in complex with known inhibitor (4-tetrazolyl pyridine sulfonamide boronic acid) was retrieved from RCSB Protein Data Bank [ 67 ] and docking was conducted on Molecular Operating Environment (MOE version 2014.09). β-Lactamases are enzymes found in outer membrane vesicles of β-lactam-resistant Escherichia coli that are able to inactivate the antibacterial properties of β-lactam antibiotics [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to perform docking, the three-dimensional X-ray crystal structure of E. coli β-lactamase (PDB ID: 4E3K, resolution = 1.43Å) in complex with known inhibitor (4-tetrazolyl pyridine sulfonamide boronic acid) was retrieved from RCSB Protein Data Bank [ 67 ] and docking was conducted on Molecular Operating Environment (MOE version 2014.09). β-Lactamases are enzymes found in outer membrane vesicles of β-lactam-resistant Escherichia coli that are able to inactivate the antibacterial properties of β-lactam antibiotics [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…These enzymes are present in the periplasmic space. Several studies indicated that they might be sequestered into MVs, and exert their protective activity on susceptible bacteria [38][39][40]. We performed an experiment that proved the presence of β-lactam degrading enzymes in the MVs of the ampicillin resistant strains of Pectobacterium.…”
Section: Discussionmentioning
confidence: 93%
“…For patients with GAS pharyngotonsillitis, this mechanism may be of a particular importance, since more than one fourth of children with GAS pharyngotonsillitis have their tonsils colonized with H. influenzae or M. catarrhalis [37], both of which can produce β-lactamase-carrying OMVs ( [22,23], this study). Mechanistically, the structural identity between the bacterial outer membrane and OMV membrane allows β-lactams to enter, through the porin channels, the OMV lumen, where β-lactamase, originating from the bacterial periplasm, is located and hydrolyzes the antibiotics [22][23][24]38]. Through this process, OMVs secreted outside bacterial cells serve as a first line of protection against β-lactams before the antibiotics reach the target bacterial population.…”
Section: Discussionmentioning
confidence: 99%